Faktor Kebertahanan Rumah Lanting di Kelurahan Kapuas Kanan Hilir - Eka Febriyani (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
A lanting house is a traditional wooden structure built above water, serving as a residence for its inhabitants who carry out daily activities within it. Living in a lanting house involves several risks related to health, safety, and security. This study aims to identify the economic factors that support the resilience of Lanting House residents along the Kapuas River in Kapuas Kanan Hilir, Sintang Village. The research was conducted in 2023 using a qualitative descriptive approach with the interactive analysis model of Miles and Huberman. Data were collected through purposive sampling of 15 residents and two key informants, employing in-depth interviews, observation, and documentation. The findings indicate that economic survival factors include the suitability of livelihood, sufficient income, affordability of living costs, and length of residence. These factors contribute significantly to why most residents continue to live in lanting houses despite the associated risks. This study offers a contextual understanding of the economic resilience of riverbank communities, which can inform local policy and spatial planning based on local knowledge and insights.